Bring-your-own container policy / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
In UiTM Sarawak, Bring Your Own Container (BYOC) is part of the waste reduction initiative to reduce the practice of single-use plastic and packaging. This is a significant step towards transitioning from single-use plastic to reusable plastic. In this response, UiTM aims to.